Public Diplomacy and the Past: The Search for an American Style of Propaganda (1952-1977) - Roth, Lois W. (Tufts Archival Research Center, 2005)
Volume 8, Issue 2. Summer From the outset, the U.S. government's decision to practice the art of propaganda has been clouded by dissension over the scope and method of its mission. Definitions of propaganda, information and cultural affairs _ the fundamental elements of public diplomacy _ have consistently been obfuscated by canny bureaucrats and congressmen. Each administration has sought to devise formulae to create a program to best meet the perceived needs of the day. The present administration is no different from its predecessors in attempting to put its own imprimatur on its public diplomacy program. Under the direction of Charles Z. Wick, the United States Information Agency's visibility has heightened. Congress has rewarded the USIA's ambitious "offensive" programming plans with increased funding, especially those targeted at television, Voice of America and exchange programs. In this article, Ms. Roth emphasizes the 45-year debate concerning which elements should or should not be included in a public diplomacy program. Such an historical approach emphasizes the still-undefined character of USIA's role. It is of particular value in lending perspective and vision to those contemplating the future nature of public diplomacy programs in a representative democracy.